Perceptions of University Teachers on Microsoft Teams for Online Instruction: A Case Study in Vietnam - Pham, Duc Thuan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
In recent years, Vietnam has experienced a surge in the popularity of online education. Microsoft (MS) Teams has been selected by numerous universities as a platform for online instruction. However, there is a scarcity of research on the perspectives of university educators on the use of this platform. This mixed-methods case study aims to examine the perceptions of Vietnamese university lecturers regarding the platform’s simplicity of use and utility in the delivery of online courses. The study also seeks to determine whether there is a substantial disparity in perceptions between male and female instructors and to investigate the obstacles associated with utilizing MS Teams for online instruction. Sixty-two instructors from a university in the northern region of Vietnam, who have expertise in teaching online courses, were provided with an online questionnaire. Additionally, semi-structured interviews were conducted with nine lecturers to gather more detailed information. According to the findings, the educators demonstrate a significant level of admiration for the platform, particularly in terms of its functionality and user-friendliness. The simplicity of learning to operate the platform is a significant distinction between the two gender categories. The results also indicate that lecturers face psychological, physical, and technological difficulties when employing the platform.